2021
DOI: 10.1002/mp.15335
|View full text |Cite
|
Sign up to set email alerts
|

Automatic quadriceps and patellae segmentation of MRI with cascaded U2‐Net and SASSNet deep learning model

Abstract: Purpose Automatic muscle segmentation is critical for advancing our understanding of human physiology, biomechanics, and musculoskeletal pathologies, as it allows for timely exploration of large multi‐dimensional image sets. Segmentation models are rarely developed/validated for the pediatric model. As such, autosegmentation is not available to explore how muscle architectural changes during development and how disease/pathology affects the developing musculoskeletal system. Thus, we aimed to develop and valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…These results fit in with the increasing application of deep learning for MR image segmentation of the knee, where it has been found that deep learning has been able to achieve consistent, accurate segmentation of structures of interest. 12,13,[27][28][29][30][31][32] However, most automated segmentation algorithms developed for the knee have focused on the cartilage, meniscus, and bones. [27][28][29][30][31][32] This may be due, in part, to some of the unique challenges associated with ACL segmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results fit in with the increasing application of deep learning for MR image segmentation of the knee, where it has been found that deep learning has been able to achieve consistent, accurate segmentation of structures of interest. 12,13,[27][28][29][30][31][32] However, most automated segmentation algorithms developed for the knee have focused on the cartilage, meniscus, and bones. [27][28][29][30][31][32] This may be due, in part, to some of the unique challenges associated with ACL segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,[27][28][29][30][31][32] However, most automated segmentation algorithms developed for the knee have focused on the cartilage, meniscus, and bones. [27][28][29][30][31][32] This may be due, in part, to some of the unique challenges associated with ACL segmentation. For example, previous semi-automated segmentation approaches faced difficulties segmenting the origin and insertion of the ACL.…”
Section: Discussionmentioning
confidence: 99%
“…U 2 -Net [ 21 24 ] is an image semantic segmentation network that combines multi-scale feature extraction and a two-level nested residual network structure. It ensures the output of high-resolution feature maps while controlling memory usage and computational costs at a lower level.…”
Section: Segmentation Of Structural Planes In Borehole Imagesmentioning
confidence: 99%
“…U-Net MRI [5,7,11,19,25,27,[31][32][33][34][35][36][37][38][39][40][41][42]44,46,55,57,64,65,89,107] US [49,100,101] CT [4,9,13,15,16,59,69,[71][72][73][76][77][78][79][80][81]83,90,91,[93][94][95]99,[103]…”
Section: Network Architecture Medical Imaging Referencementioning
confidence: 99%